PENGARUH BEBAN PAJAK, KESADARAN MEMBAYAR PAJAK DAN MEKANISME PEMBAYARAN PAJAK TERHADAP KEPATUHAN PAJAK UMKM (Students' Journal of Accounting and Banking, 2015)
This study sought to examine the effect of tax rates, tax payment mechanisms and awareness to pay tax on tax compliance of UMKM. The population in this study is Mandatory UMKM in South Semarang as many as 76 UMKM which consists of 6 villages. The population in this study is Mandatory UMKM in South Semarang as many as 76 UMKM that are in 6 villages namely Pleburan, Lamper Kidul, Central Lamper, Mugassari, Peterongan Randusari. The method of sampling is done by census sampling method ie the amount of the taxpayer population of UMKM in South Semarang entirely used as samples in this study. The results showed that the effect of tax rates on tax compliance SMEs , awareness of paying taxes affect the tax compliance of UMKM, payment mechanisms negatively affect tax compliance UMKM. The amount of tax rates, awareness of paying taxes and tax payment mechanism together - the same effect on WP Compliance.Keywords: Tax Rates, Tax Payment Mechanisms and Awareness To Pay Tax On Tax Compliance UMKM